Hot Topics in Aging Research: Protein Translation, 2009 - Kennedy, Brian K. (2009)
In the last few years, links between regulation of mRNA translation and aging have been firmly established in invertebrate model organisms. This year, a possible relationship between mRNA translation and aging in mammals has been established with the report that rapamycin increases life span in mice. Other significant findings have connected translation control with other known longevity pathways and provided fodder for mechanistic hypotheses. Here we summarize advances in this emerging field and raise questions for future studies.